THE INFLUENCE OF DIVIDEND POLICY, FUNDING DECISIONS, INSTITUTIONAL OWNERSHIP, AND LIQUIDITY ON COMPANY VALUE IN AUTOMOTIVE SECTOR MANUFACTURING COMPANIES ON THE BEI FOR THE 2018-2022 PERIOD - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
The automotive industry sub-sector and its components is one of the mainstay sectors whose development continues to be prioritized because it plays a major role in the national economy. The automotive world is developing increasingly rapidly, apart from that it is also accompanied by developments in various supporting components. This can be seen by the emergence of new innovations to attract and meet consumer needs. This research aims to determine Dividend Policy, Funding Decisions, Institutional Ownership, and Liquidity on Company Value in the Automotive sector listed on the Indonesia Stock Exchange in 2018–2022. The sampling technique used was Purposive Sampling and a sample of 9 companies from 12 was obtained. population. The research methods used are descriptive analysis techniques, multiple linear regression analysis, classical assumptions, feasibility tests, coefficient of determination, and hypothesis testing using SPSS version 21. The results of this research show that partially, the Dividend Payout Ratio variable has a positive and significant effect on Price to Book Value, while the Debt to Equity Ratio has a negative and insignificant effect on Price to Book Value, while Institutional Ownership and Current Ratio have a negative and significant effect on Price to Book Value.